Parental Perspective: The challenges and benefits of distance learning during Covid-19 - Rosdiana, Rosdiana; Aini, Rizka Marlisa (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2022)
One of the effects of the existence of Covid-19 was that face-to-face schooling could not be conducted continuously, and so another possible way of learning had to be arranged. The difference between online and face-to-face learning has invited some perceptions and obstacles to the implementation. Thus, this study aimed to describe the parents perception on the benefits and challenges towards the distance learning during the pandemic at school in Aceh, Indonesia. Thisstudy took a case in one junior high school in Banda Aceh, Aceh, Indonesia. There were 25 parents taken purposively as the sample. The study used questionnaire and interview to collect the data. The questionnaire and interview guide consisted of 10 questions posted on Google Form. The results found that the implementation of distance learning has led to the benefits and challenges. A number of challenges faced by parents when assisting their children with distance learning included lack of access to technology. Furthermore, parents had lack of knowledge or skills to assist their children with their homework, especially if the subject matter was unfamiliar. The last challenge was time constraints among the parents, making it difficult to find the time to support their children's distance learning. On the other hand, the Covid-19 pandemic has also brought significant gains toward education. The benefits were to minimize the children to be infected by the Covid-19, to engage relationship between the kids and parents, and to encourage parents to use their creativity and digital literacy in implementing the learning material.